Conserving Biodiversity in Agricultural Landscapes: A perspective on Sri Lanka - Wijesinghe, M.R. (The Institute of Biology, Sri Lanka, 2019)
Agricultural development, worldwide, is a major cause for the loss of natural forest and, consequently, of the planet’s biodiversity. In Sri Lanka, a globally recognized biodiversity hotspot, what amounts to over half of its natural forest cover was lost during the last century, and this was largely due to agricultural expansion (including raising commercial crops). Hence agricultural expansion is generally seen to be in conflict with conserving biodiversity. On the other hand, the benefits to agriculture from natural forests through their role in providing ecosystem services should be recognized – pollination, pest control, nutrient cycling, soil enrichment, water conservation. Moreover, the natural forest is a store house of genetic material that would in the future prove to be extremely valuable in the fields of agriculture and medicine. In this context, agriculture and food production and maintaining its link to conservation of biodiversity call for approaches in which agricultural systems are designed and managed giving due consideration to the conservation of biodiversity. In Sri Lanka there are several measures that could be adopted. Establishing “habitat corridors” across agricultural landscapes is important for maintaining habitat connectivity between isolated forests; this is particularly important in Sri Lanka where much of the natural forest in many parts of the country has been broken up into separate patches. The paper also goes on to describe a range of practices that can be adopted within agricultural landscapes for promoting biodiversity conservation.
Keywords: Biodiversity, sustainable agriculture, Sri Lanka